Design and develop 3-way loudspeaker system - Jusoh, Mohd. Zamri (2006)
The typical loudspeaker product is designed to make money and not necessarily to provide accurate sound reproduction. Since customers prefer small, unobtrusive speakers and judge sound quality by the amount of bass that they hear and by high frequencies they had not noticed before. There is a staggering number of essentially identical designs on the market that meet these requirements at different price. In addition current loudspeaker system technology need a large amount of investment in drivers and enclosures. So the price usually become expensive and a large number of customers could not afford to buy the prestige and high quality loudspeaker system. Furthermore in addition to achieve great and accurate sound reproduction, most manufacturer begin to use high cost material such as Aluminium , Titanium & Diamond for the drivers. For a 3-way loudspeaker which are designed perfectly, it is enough to cover the range of frequency from 20 Hertz until 20 KHertz. 3-way loudspeaker allows drivers to operate in more narrow, optimized ranges, eliminating the distortion that result from excessive driver excursion. Many advantages can be achieved especially decreasing the cost for research and production to build full range loudspeaker sound reproduction. In this project the 3-way loudspeaker system was designed and developed successfully